2023
DOI: 10.1002/adhm.202302054
|View full text |Cite
|
Sign up to set email alerts
|

Silicon‐Based Biomaterials Modulate the Adaptive Immune Response of T Lymphocytes to Promote Osteogenesis/Angiogenesis via Epigenetic Regulation

Lunguo Xia,
Tingting Wu,
Lei Chen
et al.

Abstract: Silicon (Si)‐based biomaterials have been widely applied for bone regeneration. However, the underlying mechanisms of the materials function remain largely unknown. T lymphocyte‐mediated adaptive immune response plays a vital role in the process of bone regeneration. In the current study, mesoporous silica (MS) was used as a model material of Si‐based biomaterials. It showed that the supernatant of CD4+ T lymphocytes pretreated with MS extract significantly promoted the vascularized bone regeneration. The pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Xia et al found a higher proportion of Th17 cells in mice receiving an implant of mesoporous silica particles, relative to the control group at 2 weeks, but found no differences at 4 weeks. 59 Hotchkiss et al profiled the T-helper cells around titanium implants in the femur of mice and found, in contrast to the previously cited studies, a reduced presence of Th17 cells around the implant relative to sham at 3 days. However, there were fewer differences by day 7.…”
Section: The Role Of T Cells In the Development Of The Fbrmentioning
confidence: 91%
See 1 more Smart Citation
“…Xia et al found a higher proportion of Th17 cells in mice receiving an implant of mesoporous silica particles, relative to the control group at 2 weeks, but found no differences at 4 weeks. 59 Hotchkiss et al profiled the T-helper cells around titanium implants in the femur of mice and found, in contrast to the previously cited studies, a reduced presence of Th17 cells around the implant relative to sham at 3 days. However, there were fewer differences by day 7.…”
Section: The Role Of T Cells In the Development Of The Fbrmentioning
confidence: 91%
“…Most studies, however, only study the FBR in the context of one sex. Some studies are performed only in female mice, 19,98 while others use male mice 59,60 without explaining why a specific sex was chosen. Given that sex differences can affect immune responses, an essential outcome in future studies will be to compare the FBR in both sexes.…”
Section: Challenges For Targeting the Fbr In Humansmentioning
confidence: 99%